Research of Dynamic Azimuth Gamma Instrument while Drilling for Mine - Long Chen; Gang Chen (E3S Web of Conferences, 2020)
In view of the problems that the existing gamma logging instruments in coal mines can only carry out static fixed-point measurement and are not suitable for rotary drilling, this paper, based on the analysis of the characteristics of measurement while drilling in coal mines and the principle of gamma logging, designs and realizes the dynamic gamma azimuth instruments for mines by means of power line carrier, rotation positioning and gamma measurement technology, which can measure the intensity of natural gamma ray in two directions around the borehole in real time, effectively reflect the changes of different radioactive strata, and guide the geosteering while drilling in coal mine.